The Fulling-Davies-Unruh effect - Pacheco, José A. F. (Cadernos de Astronomia, 2023)
This text (revised and upgraded) is based on graduate lectures given the author at the Côte d’Azur University on ``Different Aspects of General Relativity''. These lectures were part of a project aiming to integrate the group VIRGO in Nice (occurred in 1996), which was previously in Saclay. The present text is addressed to the Fulling-Davies-Unruh effect and its connection with the Hawking radiation, despite that both phenomena are distinct processes. The understanding of the Fulling-Davies-Unruh effect is fundamental in the field quantization on curved spacetimes, the main objective of this article.
Keywords: Unruh effect; Hawking radiation; quantum field theory